THE MODEL OF MANAGEMENT OF THE COMPETITIVENESS OF BANKING INSTITUTION - Момот, Олександр (Socio-economic relations in the digital society, 2019)
The main tendencies in the activity of banking institutions are revealed and the current factors affecting the banking competition are determined. Th e possibilities of maintaining the competitiveness of the banking institution, which depend on a certain set of factors and principles, are revealed. The necessity to identify the target competitive positions, the organizational principles of bank functioning, the methods of decision making, the methods of competitive struggle is proved. According to the model for eff ective management of its own competitive position, the banking institution should conduct an analysis of competitors’ activities. The main purpose of such an analysis should be to focus on the study of the quality and price palette of analogue products from competitors; Identification of existing and potential competitors; development of forecasts of probable strategies of functioning in the market. The constructing of a model for managing banking institutions competitiveness is designed. It is substantiated that the management of competitive advantages of the bank is carried out by developing competitive strategies, which allows forming and realizing the bank’s competitive potential. Under such a potential, it is proposed to understand the real and potential ability of the bank to develop and commercialize competitive services that by their characteristics would prevail over analogue products of other institutions. At the same time, the basis for the formation of a competitive strategy is the obligatory elucidation of priorities in the matter of liquidity and risk.